Descriptive statistics for symbolic interval-valued data - RANGANATH, H K; PRAJNESHU; GHOSH, HIMADRI (The Indian Journal of Agricultural Sciences, 2014)
It is, by now, well recognized that real data are in intervals and not in points. Unfortunately, classical statistical theory is not capable of handling data in intervals. Here, methodology for drawing univariate and bivariate histograms and computation of descriptive statistics, like sample mean and sample variance for Symbolic interval-valued data is discussed. It is hoped that researchers would start employing this type of ‘Symbolic data analysis’ to their datasets.